Evaluation of Budget Management and Financial Performance of Tambrauw Regency, Southwest Papua - Ridwan, Ridwan; Pasulu , Milka; Ismail, Azhary (International Journal of Business, Law, and Education, 2024)
This study aims to analyze the effect of budget management on the financial performance of Tambrauw Regency, Southwest Papua Province. Data collection techniques are carried out through observation, interviews, and documentation. This study uses time series data of Tambrauw Regency local government in 2018-2022, namely in the form of balance sheet report data and realization of Regional Expenditure Revenue Budget Receipts from the Badan Pengelolaan Keuangan dan Aset Daerah. Then the data analysis method uses simple linear regression analysis. The results of these findings are related to budget management as measured by the regional revenue effectiveness ratio, namely in 2018 to 2022 which shows that the budget management carried out by the local government of Tambrauw Regency, Southwest Papua Province is in a fairly effective category where the average percentage level of effectiveness of budget management for the last 5 years is 93.62%. Analysis of financial performance as measured by the ratio of regional independence, especially in Tambrauw Regency, Southwest Papua Province for the last 5 years (2018-2022) where the average independence ratio is in the range of 0.63%, so it can be said that the region is still very dependent on transfer funds from the central government. The findings in this study indicate that the better the management of the revenue budget that is transferred to the central government.